2018
DOI: 10.1021/acscentsci.8b00086
|View full text |Cite
|
Sign up to set email alerts
|

Coarctate and Möbius: The Helical Orbitals of Allene and Other Cumulenes

Abstract: As brought to the attention of the community by Hendon et al. and noted by previous workers, the π orbitals of the equilibrium geometry odd-carbon (even number of double bonds = n) [n]cumulenes may be written in either rectilinear or helical form. We trace the origins and detailed composition of the helical orbitals of cumulenes, which emerge in the simplest Hückel model and are not much modified in advanced computations. For the α,ω-disubstituted even [n]cumulenes, the helical representation is obligatory as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
190
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 64 publications
(204 citation statements)
references
References 97 publications
(248 reference statements)
10
190
0
Order By: Relevance
“…The close correspondence between Heilbronner's ideas and the SCGVB (8,9) description of the monocyclic cyclononatetraenyl cation is confirmed by the overlap integrals between the SC orbitals from Figure 3(a). As can be seen from Table 2, the overlap integrals between consecutive SC orbitals around the ring, y m y mþ1 , are all positive with the exception of y 1 h jy 9 i, Figure 3.…”
Section: Does the Electronic Structure Of Mö Bius Annulenes Follow Hesupporting
confidence: 59%
See 4 more Smart Citations
“…The close correspondence between Heilbronner's ideas and the SCGVB (8,9) description of the monocyclic cyclononatetraenyl cation is confirmed by the overlap integrals between the SC orbitals from Figure 3(a). As can be seen from Table 2, the overlap integrals between consecutive SC orbitals around the ring, y m y mþ1 , are all positive with the exception of y 1 h jy 9 i, Figure 3.…”
Section: Does the Electronic Structure Of Mö Bius Annulenes Follow Hesupporting
confidence: 59%
“…The optimized geometry was verified as a local minimum through diagonalization of the MP2/aug-cc-pVDZ analytic nuclear Hessian. Fullyvariational SCGVB (8,9) and CASSCF (8,9) calculations were carried out for the 1 1 A electronic ground state at the MP2/augcc-pVDZ optimized geometry, using the aug-cc-pVDZ and augcc-pVTZ basis sets. The differences from the B3LYP/6-311 + G(d,p) geometry reported by Mauksch et al [20] are relatively minor: As shown in Figure 3, MP2/aug-cc-pVDZ yields slightly longer carbon-carbon bond lengths.…”
Section: Does the Electronic Structure Of Mö Bius Annulenes Follow Hementioning
confidence: 99%
See 3 more Smart Citations